Anti-inflammatory Activity of Pharmaceutical Gel of Ethanolic Extract from Marine Sponge Xestospongia Sp - Wa Ode Sitti Zubaydah; Wahyuni Wahyuni; Sahidin Sahidin; Tian Amalia Halik; Rina Andriani; Astrid Indalifiany; Adryan Fristiohady (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
The aim of this study was to determine the characteristics of the gel formula based on it’s organoleptic properties, pH, viscosity, dispersion and homogenity by stability test carried out using the cycling test method and to determine the anti-inflammatory activity of the Xestospongia Sp. in male white mice (Mus musculus) by creating an artificial edema on the mice left foot induced by 1% λ-carrageenan. The gel formula from the ethanol extract of Xestospongia Sp. sponge was physically stable in terms of its organoleptic observation, homogenity, pH and viscosity test. However, the results that were obtained after dispersion test did not fulfill the requirements. In this study, the gel formula of the ethanol extract of Xestospongia Sp. sponge was administered on the mice left foot by using the variations in extract concentration of 0.02%, 0.03%, and 0.04%, and the gel without extract as a negative control and Galtaren®gel (1% Diclofenac Sodium) as a positive control. The evaluated data were in the form of mice leg edema volume measured based on its percent of inflammation and percent of inflammatory inhibition and observed for 360 minutes. The data were analyzed by using the Kruskal-Wallis test followed by the Mann-Whitney test with a confidence level of 95%. The results of this study showed that the gel formula of ethanol extract of Xestospongia Sp. sponge has an anti-inflammatory effect on each concentration and the formula that has a large anti-inflammatory effect was obtained at extract concentration of 0.04%.